2004
DOI: 10.1243/0954411041932809
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of poly-L-lactide. Part 2: Increased temperature accelerated degradation

Abstract: Poly-L-lactide (PLLA) is one of the most significant members of a group of polymers regarded as bioresorbable. The degradation of PLLA proceeds through hydrolysis of the ester linkages in the polymer's backbone; however, the time for the complete resorption of orthopaedic devices manufactured from PLLA is known to be in excess of five years in a normal physiological environment. To evaluate the degradation of PLLA in an accelerated time period, PLLA pellets were processed by compression moulding into tensile t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
149
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(164 citation statements)
references
References 29 publications
14
149
1
Order By: Relevance
“…Weir et al [Weir et al, 2004] conducted hydrolytic degradation experiments on PLLA at an elevated temperature of 50 o C and 70 o C. These studies showed that by elevating the temperature the rate of hydrolytic degradation increased exponentially, with no change in mechanism above the polymer's glass transition temperature. Samples that were hydrolytically degraded at 70 o C took only 23 days to degrade, whereas samples degraded at 50 o C took over 115 day to degrade to the same extent.…”
Section: Discussionmentioning
confidence: 99%
“…Weir et al [Weir et al, 2004] conducted hydrolytic degradation experiments on PLLA at an elevated temperature of 50 o C and 70 o C. These studies showed that by elevating the temperature the rate of hydrolytic degradation increased exponentially, with no change in mechanism above the polymer's glass transition temperature. Samples that were hydrolytically degraded at 70 o C took only 23 days to degrade, whereas samples degraded at 50 o C took over 115 day to degrade to the same extent.…”
Section: Discussionmentioning
confidence: 99%
“…At each time point every scaffold was weighed and mechanically tested allowing the degradation pathway of each individual scaffold to be followed with time. An Arrhenius equation was utilised to extrapolate results at elevated temperatures to physiological temperature [49]. …”
Section: Degradation Studymentioning
confidence: 99%
“…The degradation activation energies obtained were 87.9, 82.7 and 94.9 kJ mol −1 for LC16 : 4, LC18 : 2 and LC9 : 1 respectively. Arrhenius relation has been conducted for the change in several parameters of biodegradable polymers such as molecular weight, breaking strength, viscosity and mass loss [34,38,49,71,72]. The majority of previous publications used change in molecular weight over degradation time at different temperatures.…”
Section: Calculation Of Activation Energymentioning
confidence: 99%
See 1 more Smart Citation
“…It is often the case that polymer samples show zero mass loss for a long period at the start of degradation [15][16][17][18]. An indication of the likely duration of this delay before mass loss onset is characterised here by the time taken for water-soluble monomers and oligomers to account for 10% of the total polymer weight.…”
Section: The Effect Of Initial Molecular Weightmentioning
confidence: 99%